2000
DOI: 10.48044/jauf.2000.025
|View full text |Cite
|
Sign up to set email alerts
|

Root Barriers and Windthrow Potential

Abstract: This study was developed to determine if commercially available ribbed barriers reduce or increase the stability of trees under severe lateral stress. Green ash (Fraxinus pennsylvanica) were planted in November 1996: 6 in surrounding-type tree root barriers and 6 without barriers. Half of each group was pulled over in July 1999 under dry (14% water) soil conditions and the other half was pulled over under saturated (33% water) soil conditions. The force required to pull the trees over was measured as was the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The results for the drag load on the small branches of cedar pine (Pinus sibirica Du Tour) show a linear dependence on velocity (Orlov and Shrager 2011). In the article by Smiley et al (2000), wind loads on green trees were measured at various wind speeds. They reported that the drag load showed a linear increase with the wind speed as well.…”
Section: Introductionmentioning
confidence: 99%
“…The results for the drag load on the small branches of cedar pine (Pinus sibirica Du Tour) show a linear dependence on velocity (Orlov and Shrager 2011). In the article by Smiley et al (2000), wind loads on green trees were measured at various wind speeds. They reported that the drag load showed a linear increase with the wind speed as well.…”
Section: Introductionmentioning
confidence: 99%